2006
DOI: 10.1098/rstb.2006.1853
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysics of sweet and fat perception in obesity: problems, solutions and new perspectives

Abstract: Psychophysical comparisons seem to show that obese individuals experience normal sweet and fat sensations, they like sweetness the same or less, but like fat more than the non-obese do. These psychophysical comparisons have been made using scales (visual analogue or category) that assume intensity labels (e.g. extremely) which denote the same absolute perceived intensity to all. In reality, the perceived intensities denoted by labels vary because they depend on experiences with the substances to be judged. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
286
7
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(321 citation statements)
references
References 103 publications
23
286
7
5
Order By: Relevance
“…According to the results of the third regression model, BMI and WC could explain 5% of taste. Obesity has been linked to diets containing high levels of fat and sugar, which may have implications for taste conditions (51,52); however, Donaldson et al (53) argued that taste is only one factor among the complex causes of obesity, which corroborates with the percentage of taste predicted in our results.…”
Section: Discussionsupporting
confidence: 82%
“…According to the results of the third regression model, BMI and WC could explain 5% of taste. Obesity has been linked to diets containing high levels of fat and sugar, which may have implications for taste conditions (51,52); however, Donaldson et al (53) argued that taste is only one factor among the complex causes of obesity, which corroborates with the percentage of taste predicted in our results.…”
Section: Discussionsupporting
confidence: 82%
“…These values comprehend background correction, which was applied for each band by normalising to an adjacent region of the membrane (b). Data are presented as mean ±SEM (*p <0.05, statistically significant differences) Changes in morbidly obese women's salivary proteome performed with regard to the subjects in this study, the high enzymatic activity observed in group O may provide support for the studies reporting low levels of sweet taste sensitivity combined with strong preferences for sweet foods in obese individuals [1]. Furthermore, the small quantities of this enzyme present following bariatric surgery may be related to potential recovery of sweet taste sensitivity which had already been reported for these individuals [4].…”
Section: Discussionsupporting
confidence: 55%
“…As noted above, for salivary glucose results, higher levels of sweet molecules in saliva may mean a continuous stimulation of the taste receptors, requiring higher concentration of stimuli for sweet perception. The idea that a low sweet taste perception may be associated with higher levels of salivary amylase is, indirectly, supported by other observations: obese individuals, either rats [25] or humans [17], have increased levels of this salivary protein; at the same time, they appear to have higher preference levels for sweet foods, with the latter suggested as being associated with lower sensitivity to this taste [26].…”
Section: Discussionsupporting
confidence: 59%